Childhood obesity and the income gradient: evidence from Australia. Issue 50 (26th October 2016) - Nghiem, Son; Khanam, Rasheda
ABSTRACT: This article examines the dynamic nature of human capital formation in the context of childhood obesity and the association of household income and childhood obesity in Australia using the first five waves of the Longitudinal Study of Australian Children. Our results show a strong evidence of dynamic nature of child obesity: the lag obesity is a significant and robust predictor of obesity in the current period. We also found that the main channel for childhood obesity is inter-generational trait: the probability of obesity in children born to an obese mother or father is 15% higher than that of other children. Other important determinants are lifestyle factors, including the consumption of drinks with a high sugar content and the amount of time watching TV. Income becomes an insignificant determinant of childhood obesity once we control for unobserved individual heterogeneity.